Living traditions - Glassie, Henry, 1941-; Mahmud, Firoz, 1943- (Cultural survey of Bangladesh series ;, 2007)
Contributed articles published under the Cultural Survey of Bangladesh Project; translated from Bengali; chiefly on the handicrafts and traditional arts of Bangladesh.